Does the presence of a cantilever influence the survival and success of partial implant-supported dental prostheses? Systematic review and meta-analysis - da Silva, Emily Vivianne Freitas [UNESP]; dos Santos, Daniela Micheline [UNESP]; Sonego, Mariana Vilela [UNESP]; Gomes, Jéssica Marcela de Luna [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP] (Quintessence Publishing, 2018)
Purpose: To investigate if the presence of a cantilever influences the survival and success of partial fixed implant-supported prostheses, through a systematic review and meta-analysis, with additional analysis of the survival and marginal bone loss rates and prosthesis complications. Materials and Methods: The register protocol of the review in the PROSPERO database is CRD42016052008. The MEDLINE and Scopus databases were used for an electronic search of relevant studies up to November 2016, by means of two independent reviewers. The keywords included the combinations fixed partial denture with dental implants, and with extension or cantilever; and implant-supported dental prosthesis with extension or cantilever. The inclusion criteria were randomized clinical trials and prospective and retrospective clinical studies in English that addressed the comparison of success and survival of the use of implant-supported fixed prostheses, with and without cantilevers. Data from the selected studies were used to perform the statistical analysis. Results: Among the 408 articles identified, 4 articles met the eligibility criteria. The presence of a cantilever did not compromise marginal bone loss or the survival of the prostheses. However, minor complications were encountered for the group of partial fixed prostheses without cantilevers, with a statistical difference (P = .008). Conclusion: Cantilevers can be used in fixed prostheses and do not interfere negatively in the survival or success of the prosthesis or the marginal bone loss. However, there are minor complications when prostheses without cantilevers, or short cantilevers, are used.
Keywords: Cantilever; Dental implants; Extension; Fixed partial denture; Implant-supported dental prosthesis